Damage to the medial motor system in stroke patients with motor neglect - Migliaccio, Raffaella; Bouhali, Florence; Rastelli, Federica; Ferrieux, Sophie; Arbizu, Celine; Vincent, Stephane; Pradat-Diehl, Pascale; Bartolomeo, Paolo (Frontiers in Human Neuroscience, 2014)
Background and objectives. Motor neglect (MN) is a clinically important condition whereby patients with unilateral brain lesions fail to move their contralateral limbs, despite normal muscle strength, reflexes, and sensation. MN has been associated with various lesion sites, including the parietal and frontal cortex, the internal capsule, the lenticulostriate nuclei, and the thalamus. In the present study, we explored the hypothesis that MN depends on a dysfunction of the medial motor system by performing a detailed anatomical analysis in four patients with MN. Methods. Ten patients participated in the study: four with MN, four with left visual neglect but without MN, and three patients with left hemiplegia without MN. We used specific scales for clinical and neuropsychological assessment. We drew the lesion borders directly onto the original brain images of each patient, and plotted the lesions on anatomical atlases for grey and white matter. Results. Lesion locations were highly heterogeneous in our MN patients, and included frontal and parietal sites, basal ganglia and white matter. The only consistently damaged structure across all MN patients was the cingulum bundle, a major pathway of the medial motor system important for motor initiative, and a key connection with limbic structures crucial for motivational aspects of actions. Three MN patients with additional damage to lateral fronto-parietal networks had also signs of contralesional visual neglect. The cingulum bundle was intact in all the control patients with visual neglect or hemiplegia. Conclusions. Cingulum damage may induce MN through unilateral dysfunction of the medial motor system. Additional lateral fronto-parietal dysfunction can result in the association with visual neglect.